The Organisation for Economic Co-operation and Development's International Early Learning Study: What's going on. (June 2019) - Moss, Peter; Urban, Mathias
In this colloquium, the authors provide an update on the Organisation for Economic Co-operation and Development's proposal for an International Early Learning and Child Well-being Study, the 'first wave' of which is now being implemented in three countries: England, Estonia and the USA. The authors argue that as the International Early Learning and Child Well-being Study progresses, its superficiality and pointlessness become more apparent. They also locate the International Early Learning and Child Well-being Study in a 'global web of measurement' centred on the Organisation for Economic Co-operation and Development, whose aim appears to be the reduction of education to a purely technical exercise of producing common outcomes measured by common indicators, with the Organisation for Economic Co-operation and Development acting as the global arbiter, assessor and governor of education. They call on the Organisation for Economic Co-operation and Development and its partners to start engaging with legitimate concerns and criticisms.